Battle of AI chatbots: Graduate students’ perceptions of ChatGPT versus Gemini for learning purposes in Egyptian higher education (Journal of Applied Learning and Teaching, 2025)
The rapid developments of AI chatbots since the inauguration of ChatGPT in November 2022 have had significant impacts on higher education. The war between various AI chatbots is growing with many consequences on students’ learning journey. This study delves into this battle of AI chatbots in higher education and examines graduate students’ perceptions of ChatGPT versus Gemini, the most commonly used AI chatbots, for learning purposes. The research undertook a sequential mixed method approach with two stages of study. The first stage adopted a pretested survey using the UTAUT framework to explore graduate students’ perceptions of ChatGPT versus Gemini for learning purposes in a sample of Egyptian higher education institutions. The results informed the second stage of a qualitative study, which included in-depth interviews with a sample of graduate students who completed the survey to probe their answers and delve into the differences between these AI chatbots. Statistical SEM results using AMOS software (version 25) showed positive perceptions among graduate students’ of ChatGPT and Gemini, which significantly affected their behavioral intention and actual usage of both AI chatbots for learning purposes. However, the results of Gemini’s structural model showed more acceptance; hence, higher intention and usage than those of ChatGPT. The results of interviews showed more acceptance of Gemini over ChatGPT among graduate students with some reasons specific to the Egyptian context. Students confirmed a lack of institutional support to integrate AI for learning reasons and confirmed that their use of AI chatbots is their own choice and responsibility with informal support from their tutors. The findings of this study suggested some implications for academics and policymakers in the higher education context in order to best use these AI tools in education.